Seroprevalence of hepatitis A immunity among brazilian adult patients with liver cirrhosis: is HAV vaccination necessary? - Oliveira,Luiz Carlos Marques de (2011)
BACKGROUND: Patients with chronic liver disease have a higher risk of fulminant hepatitis when infected with hepatitis A virus, and vaccination of these patients against such infection is recommended. In Brazil, mainly in the South and Southeast regions, the epidemiology of hepatitis A (HA) has shifted from high to intermediate endemicity, which would have implication on policy of HA vaccination for these populations. OBJECTIVE: To verify the prevalence of HA immunity in adult patients with liver cirrhosis (LC), in Uberlândia MG, a city of Southeastern Brazil. METHODS: Between December 2005 and December 2006, 106 patients with LC were consecutively evaluated. In addition, 75 individuals without LC or alcoholism were evaluated (control group - CG). RESULTS: Total anti-HAV (ELISA methods) was positive in 104 (98.1%) patients with LC (82 men, 24 women; mean age, 53.3 ± 11.9 years) and in 74 (98.7%) individuals of the CG (55 men, 20 women; mean age, 47 ± 11.6 years), p > 0.05. CONCLUSIONS: For patients with chronic liver disease, in the geographic regions and age groups evaluated, routine vaccination against hepatitis A is not recommended. Moreover, the serum determination of total anti-HAV, used to assess immunity, is five times cheaper than vaccination against hepatitis A and, for this reason, should precede vaccination.